DESIGNING A WEB RESOURCE FOR STUDYING THE ARDUINO PLATFORM AS A MEANS OF GENERATING THE PROFESSIONAL COMPETENCE OF FUTURE ENGINEERS-PROGRAMMERS WITH A HIGHER EDUCATION LEVEL “MASTER” - Sherman, Michael; Samchynska, Yaroslava; Kuzheliuk, Nataliia (Journal of Information Technologies in Education (ITE), 2019)
In the context of computerization of higher education institutions, the use of electronic resources, in particular sites for educational purposes, electronic textbooks, video collections, is aimed at increasing the level of professional training of students. As electronic educational resources are an integral part of the learning process, they have an educational and methodological purpose and serve to provide educational activities for students. They are considered one’s of the key elements of the informative and educational environment. One of them is educational web resources. Using modern web technologies, the education system and, as well, further computerization can be significantly improved. This process is irreversible and compulsory. Сonsidering this, the educational web resources are the best way for improving the educational level of contemporary teachers. The article is devoted to the design of an educational web resource for the study of the platform for Arduino’s amateur design as a computer tool for the formation of professional competence of students of specialty 122 “Computer Science”, 121 “Software Engineering” at the level of higher education “Master”. The simulation of this web resource focuses on the systematization of knowledge and the development of practical design skills in the Arduino hardware computing platform when studying undergraduates of the disciplines “Quality Management of Electronic Educational Resources” and “Information Management Technologies”. In the process of designig, students determine the purpose and tasks of learning through electronic educational resources, analyze the existing analogs of the Arduino study sites, distinguish the main groups of requirements, design information architecture, present a precedent diagram for the roles specific to the website for educational purposes. The application of this topic in the educational process of the Kherson State University is aimed at developing professional competences for future programmers through the active introduction of new educational technologies, the use of opportunities for the information space, and the partnership between the teacher and the student.